2016
DOI: 10.5045/br.2016.51.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in patients with bloodstream infections during the pre-engraftment period after hematopoietic stem cell transplantation

Abstract: BackgroundBloodstream infections (BSI) remain a frequent complication during the pre-engraftment period after hematopoietic stem cell transplantation (HSCT), resulting in high mortality rates. This study evaluated risk factors for mortality in hematopoietic stem cell transplant recipients with BSI in the pre-engraftment period.MethodsThis prospective case control study was performed at the Center of Hematology and Bone Marrow Transplantation in Minsk, Republic of Belarus. Data relating to patient age and gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 11 publications
2
28
1
4
Order By: Relevance
“…Specific knowledge of resistance patterns in the HCT population is crucial as HCT patients tend to harbor more resistant bacteria compared with the general hospital population. 84 Stoma et al 83 recently showed an increase in 30 day all-cause mortality in patients who received inadequate empirical antibiotics which were defined by: (a) resistance of the isolated microorganisms to the administered antibiotics; (b) empiric antibacterial therapy that was administered 424 h after collection of blood cultures; or (c) a dosing regimen that conflicted with standard dosing recommendations. This finding underscores the importance of knowledge of the local spectrum of pathogens, which is imperative for selecting the appropriate empiric antibacterial regimen.…”
Section: Empiric Antibiotics In Febrile Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific knowledge of resistance patterns in the HCT population is crucial as HCT patients tend to harbor more resistant bacteria compared with the general hospital population. 84 Stoma et al 83 recently showed an increase in 30 day all-cause mortality in patients who received inadequate empirical antibiotics which were defined by: (a) resistance of the isolated microorganisms to the administered antibiotics; (b) empiric antibacterial therapy that was administered 424 h after collection of blood cultures; or (c) a dosing regimen that conflicted with standard dosing recommendations. This finding underscores the importance of knowledge of the local spectrum of pathogens, which is imperative for selecting the appropriate empiric antibacterial regimen.…”
Section: Empiric Antibiotics In Febrile Patientsmentioning
confidence: 99%
“…82,83 Choice of empirical antimicrobial therapy incorporates patient's clinical manifestation (severity and type of signs and symptoms associated with fever and clinical risk factors for infectious complications), disease severity, and risk factors. Specific knowledge of resistance patterns in the HCT population is crucial as HCT patients tend to harbor more resistant bacteria compared with the general hospital population.…”
Section: Empiric Antibiotics In Febrile Patientsmentioning
confidence: 99%
“…However, oncology and HSCT patients are at increased risk of developing treatment‐related toxicities such as infections, oral complications, and deconditioning. Bloodstream Infections (BSI) are the most significant cause of mortality in pediatric oncology/HSCT patients, second only to relapse . Oral complications, such as mucositis, affect up to 80% of oncology patients and have a significant impact on patient's oral function, including the basic need to eat, drink, or speak .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that the risk for BSIs, oral complications, and deconditioning can be reduced by participation in key activities of daily living (ADL), including daily bathing, physical activity, and oral hygiene. Despite this, many patients fail to perform these important ADL during their inpatient stay at a time they are most vulnerable . There is a critical need to develop robust and sustainable mechanisms to improve ADL adherence, which will prevent BSI, oral complications, and challenges related to inactivity in high‐risk immune‐compromised pediatric oncology/HSCT patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation